Neuromuscular coordination deficit persists 12 months after ACL reconstruction but can be modulated by 6 weeks of kettlebell training: A case study in women`s elite soccer - Zebis,M. K.; Andersen, C. H.; Bencke, J.; Oerntoft, C.; Linnebjerg, C.; Hölmich, P.; Thorborg, C.; Aagaard, P.; Andersen, L. L. (Case Reports in Orthopedics, 2017)
The aim of the present single-case study was to investigate the effect of 6 weeks` kettlebell training on the neuromuscular risk profile for ACL injury in a high-risk athlete returning to sport after ACL reconstruction. A female elite soccer player (age 21 years) with no previous history of ACL injury went through neuromuscular screening as measured by EMG preactivity of vastus lateralis and semitendinosus during a standardized sidecutting maneuver. Subsequently, the player experienced a noncontact ACL injury. The player was screened again following postreconstruction rehabilitation, then underwent 6-week kettlebell training, and was subsequently screened again at 6-week follow-up. Prior to and after postreconstruction rehabilitation the player demonstrated a neuromuscular profile during sidecutting known to increase the risk for noncontact ACL injury, that is, reduced EMG preactivity for semitendinosus and elevated EMG preactivity for vastus lateralis. Subsequently, the 6-week kettlebell training increased semitendinosus muscle preactivity during sidecutting by 38 percentage points to a level equivalent to a neuromuscular low-risk profile. An ACL rehabilitated female athlete with a high-risk neuromuscular profile changed to low-risk in response to 6 weeks of kettlebell training. Thus, short-term kettlebell exercise with documented high levels of medial hamstring activation was found to transfer into high medial hamstring preactivation during a sidecutting maneuver.